Co-design and implementation of community-based engineering enriched science units: Exploration of pre-service science teachers' professional development - Topcu, Mustafa Sami; Ciftci, Ayse (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
In recent years, many countries have revised their curricula to improve scientific inquiry skills and to develop the engineering practices of K-12 students, mostly within the context of science topics. However, there are not enough studies in the literature on what the content of science units integrated with en-gineering practices should be. There is also a gap in the literature regarding the kind of professional development (PD) training teachers should receive. Considering this gap, for the current study, pre-service science teachers (PSTs) developed Community Based Engineering (CBE)-Enriched Science Units within the context of a PD program. Then, they implemented these units in middle school science classes or science applications classes. The profes-sional development of the pre-service teachers during these units' development and implementation process was closely monitored and the obtained findings were presented to promote both science teacher education and engineering education. In this way, the knowledge, beliefs, attitudes, and class-room practices of PSTs regarding CBE-enriched science teaching, and their perceptions of middle school students' learning outcomes were investigated and revealed. Data were collected from 14 volunteer PSTs in a public university in Istanbul, Turkey. The data collection tools were semi-structured interviews, developed units, and reflection papers. As a result, 3 cases came to the fore: participants whose CBE-enriched science teaching self-efficacy increased (4 PSTs), remained unchanged (8 PSTs), and decreased (2 PSTs). Findings are discussed using the Interconnected Model of Professional Growth. (c) 2023 Elsevier Ltd. All rights reserved.
Keywords: Community-based engineering; Interconnected model of professional; growth; Pre-service science teachers; Education & Educational Research